HOMEPAGE FOOD AND BEVERAGE MAKING TRADITIONAL INDONESIAN USING DREAMWEAVER MX - Zaky Akbar; Marzuki Marzuki, SKom, MMSI (Jurnal Sistem Informasi, 2006)
Homepage Food And Beverage Making Traditional Indonesia aims to introduce andpreserve traditional foods and drinks among the community. Homepage design usingMacromedia Dreamweaver MX starts from the stage of determining the navigationstructure, design of the output page, how to upload to the web server and anexplanation of traditional foods and beverages as well as how to make it, good tipsfor storing food, and tips on choosing meat, fish and vegetables are good . Existingtext effect in Macromedia Dreamweaver MX Homepages pages added in order tolook more attractive homepage and more attractive and accessible globallyHomepage on the Internet after the upload, one who is using yahoo web server.